The Middle East Between the Great Powers - Petersen, T. author. aut Link
XIV, 170 p.
Keywords: Anglo-American rivalry in Egypt, Iran and the Persian Gulf in the period 1952 to 1957 represented the transfer of power in the Middle East from Great Britain to the United States. As Britain's influence in Egypt and Iran declined, its determination to hold on to the Persian Gulf increased, at one point threatening to kill any Americans found in the hotly contested Buraimi oasis. The episode is little examined by historians but played a large role in the ensuing Suez crisis.